Influence of nitrogen ion implantation on filtration of fluoride and cadmium using polysulfone/chitosan blend membranes - P. Wanichapichart (2018)
Composite membranes between polysulfone and biopolymer chitosan were produced with variations of the chitosan content and temperature during the phase inversion process. The lower chitosan content led to lower water permeability and smaller membrane cut off. When the temperature of the phase inversion process was reduced from 25 °C to 5°C, membrane pores were further decreased from somewhat greater than 10 kDa to a value smaller than 2 kDa. After being implanted with N-ions of 50 keV to a fluence of 1 × 1015ions/cm2, the composite membranes showed an improvement in the rejection by about 15% for fluoride and 10% for cadmium. In addition, a slight increase in permeation flux was observed in the ion implanted membranes. Filtration tests using the N-ion implanted membranes showed that fluoride was rejected from 100 ppm NaF solution by 47% and the rejection was increased to 60% when 2.20 ppm underground water was filtered. In the case of cadmium, the rejection was increased from 80% to 90% as an effect of the N-ion implantation.© 2014 Elsevier B.V. All rights reserved.